The experience of public hospital managers concerning the development and implementation of management strategies - NICULITA, Ana (One Health & Risk Management, 2022)
Introduction. The strategies developed by the management of public medical institutions are based on state regulations in various areas: type of services provided, human resources, etc., decisions need to be coordinated with central and/or local public authorities, to which the institution is subordinated. However, it is necessary for the process of developing and implementing strategies to include a number of mandatory steps at institutional level, which must be taken by the institution’s management. Material and methods. The aim of the study is to assess the experience of public hospital managers in developing and implementing management strategies. An assessment grid was applied for this purpose. The questions were classified into six fields: setting management strategy, added value strategy, analysis of institutional environment, institutional policies and strategic objectives, resources needed, strategy assessment. Results. In the absence of the regulation on the structure and main rules for the development of institutional strategies, the study demonstrates a very different approach of the top management regarding the strategic process in public hospitals. Conclusions. The different and sometimes erroneous approach to strategy development by the top managers results in a weak institutional strategic process.